2022
DOI: 10.2147/ijgm.s347416
|View full text |Cite
|
Sign up to set email alerts
|

FOXO4 May Be a Biomarker of Postmenopausal Osteoporosis

Abstract: Purpose Postmenopausal osteoporosis (PMOP) is a common and debilitating chronic disease, but it has just no cure options. The objective of this study was to identify genes associated with osteoporosis and reveal potential therapeutic targets. Methods Expression profiles from GSE13850 and GSE56815 datasets were combined for differential expression analysis. Extraction of intersecting genes from the combined datasets and the differentially expressed genes in GSE56814 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…40 FOXO4 is upregulated and may act as a biomarker of postmenopausal osteoporosis. 41 Inhibition of FoxO4 dampens hippocampal neuronal apoptosis, which participates in the protective role of sevoflurane against intracerebral hemorrhage. 42 The decreased mRNA expression is shown in a vasculitis model via the tumor necrosis factor-α (TNF-α) stimulation of primary human coronary artery endothelial cells (HCAECs), in which FoxO4 stabilizes endothelial cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…40 FOXO4 is upregulated and may act as a biomarker of postmenopausal osteoporosis. 41 Inhibition of FoxO4 dampens hippocampal neuronal apoptosis, which participates in the protective role of sevoflurane against intracerebral hemorrhage. 42 The decreased mRNA expression is shown in a vasculitis model via the tumor necrosis factor-α (TNF-α) stimulation of primary human coronary artery endothelial cells (HCAECs), in which FoxO4 stabilizes endothelial cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous biomarkers for PMOP had been explored and identified based on various pathogenic mechanisms of PMOP. Inflammation and the adaptive immune system had been investigated as one of the most important mechanisms 6,7 . Hong Fang et al found that the high systemic immune‐inflammation index (SII) was a high‐risk factor for POPM, indicating that the SII can not only be applied as a diagnostic biomarker but also be utilized to predict the risk of fracture incidence 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and the adaptive immune system had been investigated as one of the most important mechanisms. 6,7 Hong Fang et al found that the high systemic immune-inflammation index (SII) was a high-risk factor for POPM, indicating that the SII can not only be applied as a diagnostic biomarker but also be utilized to predict the risk of fracture incidence. 8 The increasing peripheral level of inflammatory-related molecules was found to be associated with the occurrence and severity of PMOP.…”
mentioning
confidence: 99%